High clinical suspicion of donor‐derived disease leads to timely recognition and early intervention to treat solid organ transplant‐transmitted lymphocytic choriomeningitis virus. Issue 4 (24th May 2017) - Mathur, Gagan; Yadav, Kunal; Ford, Bradley; Schafer, Ilana J.; Basavaraju, Sridhar V.; Knust, Barbara; Shieh, Wun‐Ju; Hill, Sam; Locke, Garret D.; Quinlisk, Patricia; Brown, Shelley; Gibbons, Ardith; et al.
Abstract: Despite careful donor screening, unexpected donor‐derived infections continue to occur in organ transplant recipients (OTRs). Lymphocytic choriomeningitis virus (LCMV) is one such transplant‐transmitted infection that in previous reports has resulted in a high mortality among the affected OTRs. We report a LCMV case cluster that occurred 3 weeks post‐transplant in three OTRs who received allografts from a common organ donor in March 2013. Following confirmation of LCMV infection at Centers for Disease Control and Prevention, immunosuppression was promptly reduced and ribavirin and/or intravenous immunoglobulin therapy were initiated in OTRs. The liver recipient died, but right kidney recipients survived without significant sequelae and left kidney recipient survived acute LCMV infection with residual mental status deficit. Our series highlights how early recognition led to prompt therapeutic intervention, which may have contributed to more favorable outcome in the kidney transplant recipients.